2022
DOI: 10.4067/s0717-95022022000200425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric Exercise on Muscle Architecture in Adults: A Systematic Review

Abstract: The purpose of this systematic review was to determine the effects of eccentric training on muscle architecture in the adult population. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statements were followed using keywords associated with architecture muscular and eccentric training. Four databases were used: PubMed, Scopus, SPORTDiscus and Web of Science. Methodological quality was assessed using the PEDro scale. A total of 1260 articles were retrieved, 18 included in this review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Previous studies found an increase in PA in response to concentric contraction training ( Franchi et al, 2017 ) and a reduction in FL in response to concentric exercise interventions ( Timmins et al, 2016 ), which is opposite to what occurs in eccentric interventions ( Alonso-Fernandez et al, 2020 ). However, all of these studies used more demanding exercise doses and higher volumes ( Lizama-Pérez et al, 2022 ). The increase in PA and slight decrease in FL in this study could be explained by the type of exercise used, as we considered STS to behave as a concentric loading exercise for the VL because of the need to overcome gravity during knee extension, acting mostly with a concentric component ( Frykberg & Ha, 2015 ; Franchi et al, 2017 ; Lizama-Pérez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found an increase in PA in response to concentric contraction training ( Franchi et al, 2017 ) and a reduction in FL in response to concentric exercise interventions ( Timmins et al, 2016 ), which is opposite to what occurs in eccentric interventions ( Alonso-Fernandez et al, 2020 ). However, all of these studies used more demanding exercise doses and higher volumes ( Lizama-Pérez et al, 2022 ). The increase in PA and slight decrease in FL in this study could be explained by the type of exercise used, as we considered STS to behave as a concentric loading exercise for the VL because of the need to overcome gravity during knee extension, acting mostly with a concentric component ( Frykberg & Ha, 2015 ; Franchi et al, 2017 ; Lizama-Pérez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these studies used more demanding exercise doses and higher volumes ( Lizama-Pérez et al, 2022 ). The increase in PA and slight decrease in FL in this study could be explained by the type of exercise used, as we considered STS to behave as a concentric loading exercise for the VL because of the need to overcome gravity during knee extension, acting mostly with a concentric component ( Frykberg & Ha, 2015 ; Franchi et al, 2017 ; Lizama-Pérez et al, 2022 ). PA is considered an essential factor in force production ( Lieber & Ward, 2011 ; Narici, Franchi & Maganaris, 2016 ), possibly by allowing a greater number of contractile fibers in the aponeurosis area ( Blazevich & Sharp, 2005 ).…”
Section: Discussionmentioning
confidence: 99%